(untitled) (Journal of the Entomological Research Society, 2010)
Horseflies are known worldwide as important mechanical vectors of virus, bacteria, protozoans and helminthes, which cause diseases in many wild and domestic animals, even human. Tabanidae is representing with 165 species and 13 subspecies in Turkey. In this study, 134 â™€ and 17â™‚ Tabanus terterjani (Andreva & Zeynalova, 2002) which is a new record for the Turkish fauna, were collected from different location in Turkey. The morphological characteristics are described. The taxonomical features of the species are compared with holotype specimens.